TI_GERICHTE 35.2025.41 vom 18. August 2025 , Discussa eziologia disturbi alla spalla sx. Rinvio atti per complemento istruttorio - TI Tribunale d'appello (2025)
Discussa eziologia disturbi alla spalla sx. Rinvio atti per complemento istruttorio